A Generalised Framework for Modelling Granularity. (11th May 2017) - Gyarmathy, Zsófia
Abstract: In this paper, I present a modification of the scale-based framework of Sauerland & Stateva (2007, 2011) for modelling granularity—more precisely, of the so called granularity functions. Briefly, a granularity function maps a degree of a scale to an interval containing it such that the points within that interval are mutually indistinguishable. The proposed modification is a generalisation of the original framework suited for application in a wider range of domains, and it also fares better in overcoming some formal problems in modelling granularity-sensitive phenomena and vagueness.